A NEW SNAKE MACKEREL FROM THE MIOCENE OF ALGERIA - Carnevale G. (My University, 2006)
A new genus and species of gempylid is described from the Late Miocene (Messinian) diatomite deposits of the Chelif Basin, north-east Algeria. Although its skeleton is incomplete, Chelifichthys goujeti gen. et sp. nov. possesses a unique combination of features that justifies its recognition as a new genus. Chelifichthys goujeti is characterized by remarkably elongate and serrated dorsal-fin spines, the absence of external pelvic-fin elements, and sculptured frontals and opercular bones. Chelifichthys appears to be closely related to the living genera Nealotus, Prometichthys, Rexea and Rexichthys. Chelifichthys goujeti represents the third record of the family Gempylidae in the Neogene of the Mediterranean. © 2006 The Palaeontological Association.
Keywords: ALGERIA; CHELIFICHTHYS GOUJETI; GEMPYLIDAE; LATE MIOCENE; MESSINIAN; PERCIFORMES; TELEOSTEI; Cenozoic::Neogene::Miocene::Messinian; Кайнозой::Неоген::Миоцен::Мессинский